2017
DOI: 10.1111/aogs.13169
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic accuracy of polymerase chain reaction for intrapartum detection of group B streptococcus colonization

Abstract: The PCR test has sufficient accuracy to direct intrapartum antibiotic prophylaxis for GBS transmission during delivery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
10
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 10 publications
5
10
1
Order By: Relevance
“…A total of 89 samples that tested positive by culture (regardless of whether they are positive or not by any of the PCRs) and/or positive by both PCR techniques (although negative by culture) were considered true positives, giving an overall detection rate of 27.81%. The GBS detection rated reported in this study was slightly higher compared to previous studies in Spain [ 17 , 21 ], but in agreement with the SGB prevalence reported in different studies performed in Europe [ 7 , 34 , 35 ]. According to previous studies, the detection rate for GBS ranged between 10 and 35% [ 4 , 7 , 22 , 36 ].…”
Section: Discussionsupporting
confidence: 92%
“…A total of 89 samples that tested positive by culture (regardless of whether they are positive or not by any of the PCRs) and/or positive by both PCR techniques (although negative by culture) were considered true positives, giving an overall detection rate of 27.81%. The GBS detection rated reported in this study was slightly higher compared to previous studies in Spain [ 17 , 21 ], but in agreement with the SGB prevalence reported in different studies performed in Europe [ 7 , 34 , 35 ]. According to previous studies, the detection rate for GBS ranged between 10 and 35% [ 4 , 7 , 22 , 36 ].…”
Section: Discussionsupporting
confidence: 92%
“…Although the revised CDC guidelines [1] recommend universal culture-based GBS screening between 35 and 37 weeks of pregnancy, the use of molecular methods as an additional rapid method of detection is encouraged. In concordance to our data, increased GBS detection rates by PCR assays compared to culture have been previously reported [15,23] with comparable results [5,6,8,24] or with lower colonization rates than the ones observed in this study [25]. However, previous data showed comparable performance of PCR method to culture [14].…”
Section: Discussionsupporting
confidence: 93%
“…It is reported that the antenatal microbiological screening test has the sensitivity of about 60% and a relatively low specificity [16,[19][20][21]. Our studies confirmed a high sensitivity of intrapartum PCR assay when compared to antenatal culture, which is consistent with other studies [22][23][24][25]. This result is important because as it has been shown in Young et al report, majority of newborns with sepsis was born from women with GBS negative antenatal screening test and subsequently without the IAP [18].…”
Section: Discussionsupporting
confidence: 92%